L’Ungheria nelle memorie di primo Ottocento del conte modenese Luigi Forni - Righi Guerzoni, Lidia (Verbum – Analecta Neolatina, 2022)
The essay analyses Count Luigi Forni’s experiences in the Kingdom of Hungary, based on his work Alcune notizie sull’Ungheria. His experiences as a young military officer in several Hungarian garrisons forged in Count Forni a lifelong bond with Hungary. After a comprehensive description of the chorography, which is also in print, the essay discusses Count Forni’s manuscript legacy, including manuscript notes of the rapidly developing capital, Budapest, written during a later visit to the military and the publication of the chorography. Count Forni’s relationship with Hungary concludes with opinion pieces written after the defeat of the 1848–1849 War of Independence.